(untitled) (Research, Society and Development, 2022)
This work proposes to analyze, through doctrine and jurisprudence, whether it is possible to exclude a unit owner who is considered antisocial due to repeated antisocial behavior in view of the limitations imposed by the right to property, whether due to violation of the social function, or for prohibition of the abuse of the right, or even in favor of the neighborhood right. In building condominiums, given the proximity of the autonomous units and the necessary coexistence in common areas, measures must be adopted that promote peace between neighbors, which are established by condominium rules (Convention and Internal Regulation) that seek to maintain peace and harmony in the condominium life. In this context, this article seeks to analyze whether, in the face of serious and repeated behavior, it would be possible to exclude the antisocial condominium from the building condominium. The essence of this article is to expose the limitations of property rights due to its social function, address the concept of "antisocial joint owner", address condominium rules and analyze the possibility of their exclusion from the building condominium, through legal provisions, doctrinal positions and court decisions that deal with the matter, in order to support the information collected and presented here.